Clinical profile of cardiac myxoma: 11 years experience of 90 cases (Bangladesh Heart Journal, 2016)
Introduction: Cardiac myxoma is a benign neoplasm that represents the most common primary tumour of the heart. Because of nonspecific symptoms, early diagnosis may be a challenge. Although the left atrium is the most commonly involved site of origin in 75% of cases, it can arise from any of the cardiac chambers. Symptoms from a cardiac myxoma are more pronounced when the myxomas are left-sided, racemosus, and over 5 cm in diameter. Symptoms are produced by mechanical interference with cardiac function or embolization. Being intravascular and friable, myxomas account for most cases of tumor embolism. The site of embolism is dependent upon the location (left or right atrium) and the presence of an intracardiac shunt. Most atrial myxomas are benign and can be removed by surgical resection.Objectives: To see clinical presentation and echocardiographic profile of cardiac myoxomas.Methods: 90 cardiac myxoma patients who admitted both in cardiology and cardiac surgery departments of National Institute of Cardiovascular Diseases (NICVD), Dhaka from August 2003 to July, 2014 were studied clinically and by echocardiogram. Clinical histories were reviewed, noting age, gender, and clinical presentation.Results: There were 30 males and 60 females, ages ranged from 17 to 76 years. The commonest clinical feature was dyspnoea (94.44%), followed by palpitation (76.67%), chest discomfort (74.44%), constitutional symptoms (50%), pedal oedema (20%), syncope (14.44%), and embolization (7.7%). The mean duration of symptoms was 09.7 months.Conclusion: The clinical presentation of cardiac myxoma is often nonspecific, so high index of clinical suspicion is important for its early and correct diagnosis. The size and appearance of the myxomas correlated with the presenting symptoms.Bangladesh Heart Journal 2016; 31(1) : 18-22